Brown trout spawning habitat selection and its effects on egg survival. Issue 1 (27th October 2015) - Gauthey, Zoé; Lang, Margaret; Elosegi, Arturo; Tentelier, Cédric; Rives, Jacques; Labonne, Jacques
Abstract: Salmonid females invest heavily in reproduction, through gamete production, habitat selection and maternal care. Habitat selection and maternal care are expected to provide shelter for eggs against scouring and predators. However, females also tend to produce variable egg sizes, and this trait may interact with habitat quality to influence the survival of offspring. In this study, we aimed at evaluating the role of female habitat selection on egg survival conditional on individual egg size and female body size. We monitored female reproductive activity in two natural rivers for 3 years, in order to relate nest characteristics to female body size. Bigger females dug deeper nests at lower shear stress force. Right after the end of nest construction, we sampled a part of the eggs laid by each female, measured them individually, and placed them back using capsules within their original position in the nest. At time of hatching, the capsules within the nest were collected and individual egg mortality was assessed. Our results indicate that scouring was the main driver for mortality (75%) and that nest burial depth and shear stress force above the nest both influenced scouring. However, subsequent survival was influenced by neither nest characteristics, individual egg size, nor the interaction between both. It is therefore expected that traits or tactics that reduce nest scouring probability should be under strong selection.